“CONFESSIONS” BY J.-J. ROUSSEAU: TECHNIQUES OF AESTHETIC INFLUENCE AND STRATEGY OF READER’S RECEPTION - Olena K. Cherniavska; Iryna Ye. Rozhdestvenska (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2024)
The study aims to explore the specific features of the modern reception of J.-J. Rousseau’s “Confessions”. The theoretical framework of the research is grounded on the ideas advanced by T. Avtuxovych, M.Czermińska, M.Głowiński, W.Iser, R. Jakobson, H.R.Jauss, P.Lejeune, Yu. Lotman, V.Tjupa, Zh. Starobinskiy and other scholars. The researchers describe the semiotic model of literary communication and the theory of the text by Yuri Lotman. The research was conducted using historic-functional, hermeneutic, receptive, and theoretical analysis methods. An attempt is made in this paper to show how the process of “decoding” the meanings intended by the author in the text takes place. In particular, the authors study how Rousseau’s “Confessions” functions in the structure of modern literary communication. The specific objectives of the present study are the meanings of “Confessions” are read by the contemporary recipient and which ones are relegated to the background compared to the literary communication of the eighteenth century. The common discourse code of the author and the reader is the key to successful communication and understanding of the specifics of the project of Rousseau’s life writing. At the same time, the success and specificity of artistic communication are influenced by the difference in discourse code meanings related to the time distance between the author and the recipient and the layering of new historical and cultural patterns in the reader’s consciousness. At the thematic level, three main themes are considered, including: a) the social origin of the autobiographical subject, b) his conflict with society, and c) the protagonist’s intimate self-disclosure. Thus, the article provides a detailed examination of the motif of the social origin of the autobiographical character. On the topic of the social origin of the character, instead of the plebeian’s right to public attention for the contemporary reader, the value of education and knowledge, freedom of speech and individual liberty are being actualised. Of particular note is the theme of the conflict between a character and society, the idea of the human right to otherness, the right to personal liberty and the right to choose the concept of one’s own life comes to the forefront. Thus, a literary text realises the social function of literature. The reading of the character’s self-disclosure by an attentive reader (from Rousseau’s contemporary to modern readers) has a twofold purpose: first, to encourage everyone to live the experience of the character and thus to think about themselves, and second, to reflect on society as a whole. It testifies to the fact that in the aspect of self-disclosure of the meaning of “Confessions”, the transformation of confession as an external form of a religious rite of repentance addressed to God into the narrative genre of confessional autobiography addressed to a human reader of the story is actualized. The study demonstrated a need for continuation of the study in the aspect of reader reception to contribute to the perception of its place in the contemporary literary and cultural space.